Analisis Faktor Yang Mempengaruhi Kinerja Karyawan Ekspedisi Muatan Kapal Laut PT. Internasional Fortuna Eksperindo Semarang Indah - Kusdibyo (Yayasan Literasi Sains Indonesia, 2022)
The purpose of this study is to analyze and explain the effect of work motivation, work experience, and work environment, on the performance of employees of PT. International Fortuna Eksperindo Semarang Indah. Work motivation is a change in energy in a person (personal) someone which is characterized by the emergence of feelings and reactions to achieve goals, the overall driving force in employees that causes work activities. The population of this study were employees of PT. International Fortuna Eksperindo Semarang Indah, totaling 65 people. The sample consisted of 65 respondents who were taken by the saturated method. Data analysis using multiple regression and hypothesis testing and using SPSS. The results of this study based on multiple linear regression analysis that there is an influence between the three independent variables, namely work motivation, work environment, and work experience on employee performance at PT. International Fortuna Eksperindo Semarang Indah. This is also evidenced by the hypothesis test obtained that partially that work motivation, work environment, and work experience have a positive and significant effect on the performance of employees of PT. International Fortuna Eksperindo Semarang Indah.